The Need for Efficient Land Use During Water Shortage in Karakalpagist (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
In recent years, the process of land degradation in the Republic of Karakalpakstan is intensifying. The main reasons for this are the shortage of water, the decrease in water demand for agriculture by 39-41% in 1999-2001, by 50-55% in 2007-2010, and by 54-58% in recent years. pouring, worries humanity.